Peranan Orang Tua Terhadap Perkembangan Pendidikan Anak Dalam Keluarga Kristen - Claartje Pattinama (Jurnal Ilmiah Wahana Pendidikan, 2020)
Education today is indeed a serious concern of every individual. This explains that each individual is eligible to go to school so that later they will get a better level of progress. Because that's the best way to get a good education, it must be done in various ways by each individual, who certainly has his own way to be able to develop it. Therefore, in this writing. Clearly want to direct how the role of parents in the development of children's education in the midst of the Christian family, so that with the role of parents in each process of children's education, especially in the implementation of Christian Religious Education in the family, children can achieve a better future. On the other hand the role of parents in children's Christian education in the family is very important, in efforts to raise, educate, and guide their children, and are required to build a family or household in order to motivate children to try and do good. This illustrates that as Christian parents, they must be able to take responsibility in developing each child's inner development and set an example so that children can grow in the Christian faith and fear God.